Odpowiedzi

2009-10-04T18:10:47+02:00
A)
{2x-y=2
{x+y=7
3x = 9
x = 3 --> y = 4

b)
{x+y=5
{-x+2y=4
3y = 9
y = 3 --> x = 2

c)
{2x+y=3
{-3x+y= -2 /*(-1)

{2x+y=3
{3x-y= 2
5x = 5
x = 1 --> y = 1

d)
{x+ 0,5 y = 4 /*(2)
{2x - y = 4

{2x + y = 8
{2x - y = 4
4x = 12
x = 3 --> y = 2

e)
{2x+2y= 3 (x-y) +4
{4(x + y ) - 4 = 7 (x-y)

{2x + 2y = 3x - 3y + 4
{4x + 4y - 4 = 7x - 7y

{-x + 5y = 4 /*(-3)
{-3x + 11y = 4

{3x - 15y = -12
{-3x + 11y = 4
-4y = -8
y = 2 --> x = 6

f)
{6x+y=8
{-6x+4y-2 = 0

{6x+y=8
{-6x+4y = 2
5y = 10
y = 2 --> x = 1
1 5 1